2023
DOI: 10.3390/polym15020250
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Stretchable, Dry-Resistant MXene Nanocomposite Conductive Hydrogel for Human Motion Monitoring

Abstract: Conductive hydrogels with high electrical conductivity, ductility, and anti-dryness have promising applications in flexible wearable electronics. However, its potential applications in such a developing field are severely hampered by its extremely poor adaptability to cold or hot environmental conditions. In this research, an “organic solvent/water” composite conductive hydrogel is developed by introducing a binary organic solvent of EG/H2O into the system using a simple one-pot free radical polymerization met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In Figure S1, it can be observed that the (002) peak in Ti 3 C 2 T X shifts to a small angle and broadens by comparing the XRD patterns of Ti 3 AlC 2 and Ti 3 C 2 T X , and the characteristic peak of Al at 38.7°is weakened, illustrating that most of the Al in the MAX has been etched away. 39 The elemental composition and chemical state of MXene nanosheets can be observed in Figure 2F XPS spectra; the presence of Ti, O, C, and F elements in MXene nanosheets was confirmed. In the high-resolution XPS spectrogram Figure S2A of the C 1s of Ti 3 C 2 T X , the peak of 41 The above results demonstrate the successful preparation of MXene.…”
Section: Synthesis and Characterization Of Hydrogelmentioning
confidence: 80%
“…In Figure S1, it can be observed that the (002) peak in Ti 3 C 2 T X shifts to a small angle and broadens by comparing the XRD patterns of Ti 3 AlC 2 and Ti 3 C 2 T X , and the characteristic peak of Al at 38.7°is weakened, illustrating that most of the Al in the MAX has been etched away. 39 The elemental composition and chemical state of MXene nanosheets can be observed in Figure 2F XPS spectra; the presence of Ti, O, C, and F elements in MXene nanosheets was confirmed. In the high-resolution XPS spectrogram Figure S2A of the C 1s of Ti 3 C 2 T X , the peak of 41 The above results demonstrate the successful preparation of MXene.…”
Section: Synthesis and Characterization Of Hydrogelmentioning
confidence: 80%
“…With the rapid rise and development of wearable electronic devices, the demand for high-performance flexible sensors is increasing. Flexible strain sensors have attracted extensive research attention in recent years, and have shown broad application prospects in the fields of motion monitoring, medical equipment, consumer electronics, electronic skin and soft robots [1][2][3][4][5][6]. For example, in prosthetics and robotics applications, strain sensors can monitor the bending of joints, fingers, etc., in order to achieve health status assessment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Conductive hydrogels have a wide range of promising applications in electronic skin, 1,2 wearable sensors, [3][4][5][6][7] soft robotics, [8][9][10] and human-computer interaction 11,12 due to their unique flexibility and efficient, low-cost manufacturing process. 13 Conductive hydrogels made of hydrophilic polymers have superior mechanical flexibility, 14,15 biocompatibility, 16 and electrical conductivity, enabling them to mimic various skin functions accurately.…”
Section: Introductionmentioning
confidence: 99%